1967
DOI: 10.1002/jhet.5570040111
|View full text |Cite
|
Sign up to set email alerts
|

Oxazolo[3,2‐a]pyridinium salts

Abstract: The first synthesis of the aromatic oxazolo[3,2‐a]pyridinium ring system has been accomplished by the cyclization of 1‐acetonyl‐ or 1‐phenacyl‐2‐pyridones. Through use of the analogous quinolones and 2‐(p‐bromophenacyl)‐1‐isoquinolone, benzologs of the new system have been prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…It is also well known, that in sulfuric acid the compound XlVa undergoes closure of the oxazolium ring forming 2-phenyloxazolo[3,2-a]pyridinium cation Xb [12]. We found that the conversion of mesoionic derivative XII to cation Xb may proceed as one-pot recyclization [13] with the yield 83%, and the structure of the perchlorate Xb was confirmed by X-ray data.…”
Section: Structure Of B-fused Munchnonessupporting
confidence: 68%
“…It is also well known, that in sulfuric acid the compound XlVa undergoes closure of the oxazolium ring forming 2-phenyloxazolo[3,2-a]pyridinium cation Xb [12]. We found that the conversion of mesoionic derivative XII to cation Xb may proceed as one-pot recyclization [13] with the yield 83%, and the structure of the perchlorate Xb was confirmed by X-ray data.…”
Section: Structure Of B-fused Munchnonessupporting
confidence: 68%
“…The sole described example is the synthesis of angular salt 4a on using 1-methoxyisoquinoline (7a) [10]. The homologous salt 4b is unknown, and information on linear tricyclic system 3 is generally absent from the literature.…”
mentioning
confidence: 99%
“…The N-phenacylation of 1-methoxyisoquinoline 7a in low yield (~8%) has been described [10]. Examples of the N-alkylation of the homologous isoquinolone 6b or the methoxy derivative are unknown, although an unusual intramolecular N-alkylation, accompanying O-demethylation, for the structurally analogous 1-methoxy-3-(ω-bromopropyl)isoquinoline has been described [15] There are few examples of N-alkylation among derivatives of 3-isoquinolone 8a and also of 3-methoxyisoquinoline 9a.…”
mentioning
confidence: 99%
See 2 more Smart Citations